A Registry for Patients With Asplenia/Hyposplenism Reduces the Risk of Infections With Encapsulated Organisms. (17th February 2018) - Arnott, Alicia; Jones, Penelope; Franklin, Lucinda J; Spelman, Denis; Leder, Karin; Cheng, Allen C
Abstract : We linked data from a registry for people with asplenia with a statewide notifiable diseases database. We found that registration was associated with a 69% reduction in the risk of infection with encapsulated organisms. Abstract: Background: Overwhelming post-splenectomy infection (OPSI) is a serious complication of asplenia. Clinical guidelines recommend numerous measures to reduce the risk of OPSI, but awareness and adherence to preventative measures are generally poor. We aimed to determine whether a registry for asplenic/hyposplenic patients was associated with a reduction in the incidence of infection with encapsulated bacteria. Methods: We performed a retrospective cohort study of asplenic/hyposplenic patients in the state of Victoria, Australia, who registered with Spleen Australia from 2003 through 2014. Spleen Australia provides education, clinical guidance, and annual vaccination reminders to registrants and their healthcare providers. We compared the incidence of infection with Streptococcus pneumoniae, Haemophilus influenzae type B (Hib), and Neisseria meningitidis before and after registration. Registry data were linked with Victorian notifiable disease data on invasive pneumococcal disease (IPD), invasive meningococcal disease (IMD), and Hib between 2000 and 2014. Results: Twenty-seven cases of IPD and 1 of IMD occurred among 3221 registrants. No cases of Hib were reported. The rate of IPD/IMD was 150 per 100000 patient-years prior to registration and 36 per 100000 patient-years after registration; registration was associated with a 69% reduction in the risk of infection (incidence rate ratio, 0.31; 95% confidence interval, 0.12 to 0.83; P = .019). Based on the absolute reduction in incidence, we estimate that Spleen Australia prevents 5–6 invasive infections with encapsulated organisms annually among registrants. Conclusions: Systematic, long-term approaches to post-splenectomy care can significantly reduce the risk of infection with encapsulated organisms among individuals with asplenia/hyposplenism.